Kohesi Gramatikal dan Leksikal pada Caption Postingan Akun Instagram @fauzanalrasyid - Hastuti*, Khayya Meiliina Eka; Sabardila, Atiqa (Universitas Suryakancana, 2025)
This article describes grammatical and lexical cohesion in Instagram account post captions. Type of descriptive qualitative research with a content analysis approach. The data and data source are the captions of the Instagram account @fauzanalrasyid, which were published in the period 26 June to 28 August 2024 in the form of words, phrases, and complete sentences in the discourse. The technique used is the note-taking technique and content categorization based on its types. The data analysis used was transcribed and reduced through the researcher's diligent observations and presented in the form of a narrative explanation. The results of this research found 30 data with 40 quotations. The use of grammatical cohesion appears 23 times, and lexical cohesion appears 17 times. Then, it can be concluded that the owner of the Instagram account @fauzanalrasyid is a public figure who has good communication skills, is careful in conveying messages, is positive in communicating, and is professional in managing his social media content as a